A Analisis Perbandingan Kinerja Keuangan Bank Konvensional Dan Bank Syariah Yang Terdaftar Di Bursa Efek Indonesia (BEI) Periode 2021-2024: Analisis Perbandingan Kinerja Keuangan Bank Konvensional Dan Bank Syariah Yang Terdaftar Di Bursa Efek Indonesia (BEI) Periode 2021-2024 - Sulisna, Mega; Haitamy, Eri Bestary Al; Saputra, Ferdyan Wana (Journal of Applied Accounting And Business, 2025)
This study aims to analyze the comparison of the financial performance of conventional banks and Islamic banks listed on the Indonesia stock exchange using financial ratios. The method used in this study is quantitative descriptive with a purposive sampling approach, which resulted in six companies as research samples. The data used was obtained from the company's financial statements reported in Rupiah. The results of the study show that there is a significant difference in the analysis of banking financial ratios compared to their financial performance. This research is expected to contribute to a deeper understanding of the relationship between financial ratios and financial performance of companies